At-Tanzil Sebagai Metode Akselerasi Keterampilan Membaca Al-Qur’an Anak Usia Dini - Halimah; Ali Rahmat (Lembaga Penelitian dan Pengabdian Institut Kariman Wirayudha Sumenep, 2023)
The skill of reading the Qur'an is very important for humans, especially Muslims, being skilled in reading the Qur'an is of course very important, therefore the researcher provides the application of the At-Tanzil method to students so that children's Al-Qur'an reading skills are even better. therefore the purpose of this study is to describe: 1) To find out the application of the At-Tanzil method juz 1 and 2 in improving Al-Qur'an reading skills. 2) To determine student achievement in applying the At-Tanzil Method juz 1 and 2 in improving Al-Qur'an reading skills, the method used in this study is a qualitative descriptive method, research data obtained using observation, interview and documentation techniques. The objects of research are school principals, teachers and parents of RA Mambaul Hikmah students. Data analysis is done by compiling data; connecting data, reducing, presenting data, then concluding Data validity assurance techniques are based on four categories, namely: credibility test (trust), transferability (transferability), dependability (dependency) and confirmability (certainty), tested by triangulation. and on the results of the study using two findings, namely the first implementation (planning, implementation, and evaluation), the second, namely the achievements achieved by children